Customer Satisfaction as a Mediator of Service Quality and Experiential Marketing on Online Transportation Loyalty - Erny Amriani Asmin; Yulianingsih Yulianingsih; Taristania Lupita (Jurnal Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study analyzes the direct and mediating influences of service quality, experiential marketing, and customer satisfaction on brand loyalty in the context of online transportation services in Bogor City. Methodology/approach: Using a quantitative approach, data were obtained from 100 respondents determined using the Lemeshow formula and purposive sampling. The questionnaires were administered directly to the users of online transportation services. The collected data were analyzed using descriptive, associative, and path analysis techniques in SPSS version 25. Results/findings: The findings indicate that both service quality and experiential marketing significantly impact customer satisfaction and brand loyalty. In addition, customer satisfaction has a positive influence on brand loyalty. However, customer satisfaction only served as a mediating variable in the relationship between experiential marketing and brand loyalty, and not in the relationship between service quality and brand loyalty. Conclusions: Service quality and experiential marketing are crucial for enhancing customer satisfaction and brand loyalty. Positive experiences are stronger drivers of satisfaction and loyalty. Limitations: The use of purposive sampling, a relatively small sample size, and the study’s focus on Bogor City may limit its generalizability. Contributions: This study provides empirical evidence of the mediating role of customer satisfaction and practical insights for service providers to improve customer experience. This study also enriches the consumer behavior literature by emphasizing the role of experiential marketing and satisfaction in fostering brand loyalty.